ISOLATION AND STRUCTURAL ELUCIDATION OF AN ALKALOID FROM THE RESIN OF Maquira coriacea (Karsten) Cc.Berg - Monsalve Ocmin, Luis (2022)
The resin of the Maquira coriacea is popular in traditional medicine in the communities of Peru, currently lacking phytochemical studies; therefore, the objective of the investigation is to isolate and elucidate the alkaloids present. The resin was subjected to hydroalcoholic extraction by maceration, and 2 alkaloids were extracted, one was isolated and identified with a retention factor (Rf2) 0.97. The wavelengths (λ) reported in ultraviolet visible spectroscopy (UV-VIS) were λ=226 nm maximum and λ=260 nm minimum; 1H, 13C andtwo-dimensional nuclear magnetic resonance (NMR) chemical shifts (δ) report characteristic shifts for bis-benzylisoquinoline alkaloids, and Hybrid Quadrupole Time High Resolution Mass Spectrometry (HRMS-Q) gave a mass of m/s =758.31, allowing the identification of a taligrisin-type base bis-benzylisoquinoline alkaloid (M. Coriacina). Finally, the total alkaloid content of 175 mg of Atropine (AT)/100g of Maquira coriácea resin is reported.